MENGETAHUI PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP VOLUME PENJUALAN PADA UD. SELLA KECAMATAN FANAYAMA KABUPATEN NIAS SELATAN - Agnes Santriawati Gee (Universitas Nias Raya, 2024)
This study aims to determine the effect of product quality and price on sales volume at UD. Sella, Fanayama District, South Nias Regency. This type of research is associative quantitative research. The sample used in this study amounted to 30 people. The analytical method used is multiple linear regression analysis. The results of this study indicate that there is a significant influence between product quality and price variables on sales volume. The results of this study obtained a multiple linear regression equation, namely: Y = 14.319 + 0.231X1 + 0.415X2. Partially obtained t value for product quality variable t count of (2.510) > t table (1.701) and a significant level of 0.018 <alpha level of 0.05 for the price variable t count of (3.571) > t table (1.701) and a significant level 0.001 < 0.05 alpha level. Then simultaneously the calculated F value is (10.330) > F table (3.343) and an R square value of 0.433 or 43.3% is obtained. So it can be concluded that product quality and price have a significant effect on sales volume at UD. Sella, Fanayama District, South Nias Regency.